International Legal Challenges in Regulating Asymmetric Armed Conflicts - Kudryavtsev, Vladislav; Kolganov, Sergei; Sitnikova, Oksana; Chikaeva, Karina; Akhyadov, Elman (Jurnal Cita Hukum, 2025)
The purpose of the article was to analyze the international legal aspects of asymmetric armed conflicts, including the right to self-defense and the legal status of civilians. The methodological basis of the study consists of an examination of international legal instruments, such as the UN Charter, the Geneva Conventions and their Additional Protocols. Additional literature review included contemporary conflict studies and international humanitarian law. Results showed that asymmetric conflicts blur the line between combatants and civilians, complicate the application of proportionality, and diminish the effectiveness of classical jus ad bellum and jus in bello norms. The conclusion highlights the need to adopt international law to the involvement of non-state actors and to the growing number of cases in which states invoke preventive self-defense, while ensuring strict compliance with its legal criteria.